Cepas do complexo Candida parapsilosis de origem animal : classificação taxonômica, sensibilidade antifúngica e atributos de virulência in vitro - Rodrigues, Terezinha de Jesus Santos (2013)
In the past decades, important changes in the epidemiology of fungal infections have resulted in the frequent isolation of yeasts of the genus Candida. Yeasts of the Candida parapsilosis species complex, for example, have been pointed out as infectious agents and components of the microbiota of animals. Thus, the work aimed at identifying molecularly the strains of the C. parapsilosis species complex recovered from veterinary sources and maintained at the Specialized Medical Mycology Center, as well as evaluating their in vitro antifungal susceptibility profile and attributes of virulence. For such, 28 strains of the C. parapsilosis species complex, recovered from dogs, psittacines, raptors and prawn were assessed. Initially, the strains were phenotypically identified, based on their morphological and biochemical characteristics, which confirmed their identification as C. parapsilosis lato sensu. The molecular identification of the strains was then carried out through PCR-REA. In order to analyze the in vitro antifungal susceptibility, the broth microdilution assay was performed, according to the document M27-A3 of the Clinical Laboratory Standards Institute (CLSI) 2008, using amphotericin B, itraconazole, voriconazole, fluconazole and caspofungin. Concerning the virulence attributes, the ability of producing phospholipase was evaluated on egg yolk agar, while protease production was assessed on bovine serum albumin agar, and biofilm formation was tested in 96-well polystyrene microplates. The genotypical analysis identified 13 C. parapsilosis stricto sensu, ten C. orthopsilosis and five C. metapsilosis. The minimum inhibitory concentrations varied from 0.125 to 1 μg/mL foramphotericin B, from 0.03125 to 0.5 μg/mL, for itraconazole, from 0.03125 to 0,25 μg/mL for voriconazole, from 0.5 to 16 μg/mL for fluconazol and from 0.0625 to 2 μg/mL for caspofungin. Fluconazole resistance was observed in three strains of C. parapsilosis stricto sensu and two of C. metapsilosis, while one strain of C. parapsilosis stricto sensu and five C. orthopsilosis presented high MIC values for caspofungin (2 μg/mL). As for the virulence attributes, none of the tested strains produced phospholipases, while 23/28 presented proteolytic activity, and all of the strains produced biofilm, with one weak producer, 20 moderate producers and seven strong producers. These data show that the in vitro antifungal susceptibility and production of virulence attributes vary among species of the C. parapsilosis species complex, which can lead to differences in pathogenicity and therapeutic response.